Species-, organ- and cell-type-dependent expression of SPARCL1 in human and mouse tissues. - Klingler, Anika; Regensburger, Daniela; Tenkerian, Clara; Britzen-Laurent, Nathalie; Hartmann, Arndt; Stürzl, Michael; Naschberger, Elisabeth (PLoS ONE, 2020)
SPARCL1 is a matricellular protein with anti-adhesive, anti-proliferative and anti-tumorigenic functions and is frequently downregulated in tumors such as colorectal carcinoma or non-small cell lung cancer. Studies have identified SPARCL1 as an angiocrine tumor suppressor secreted by tumor vessel endothelial cells, thereby exerting inhibitory activity on angiogenesis and tumor growth, in colorectal carcinoma. It is unknown whether SPARCL1 may exert these homeostatic functions in all organs and in other species. Therefore, SPARCL1 expression was comparatively analysed between humans and mice in a systematic manner. Murine Sparcl1 (mSparcl1) is most strongly expressed in the lung; expressed at an intermediate level in most organs, including the large intestine; and absent in the liver. In human tissues, SPARCL1 (hSPARCL1) was detected in all organs, with the strongest expression in the stomach, large intestine and lung, mostly consistent with the murine expression pattern. A striking difference between human and murine tissues was the absence of mSparcl1 expression in murine livers, while human livers showed moderate expression. Furthermore, mSparcl1 was predominantly associated with mural cells, whereas hSPARCL1 was detected in both mural and endothelial cells. Human SPARCL1 expression was downregulated in different carcinomas, including lung and colon cancers. In conclusion, this study revealed species-, organ- and cell-type-dependent expression of SPARCL1, suggesting that its function may not be similar between humans and mice.